Influence of Promotion on the Job Performance of Police - Saguda, Mndeke; Onyancha, Hezron; Amos, Amembah A. Lamu (Business Management and Strategy, 2024)
The study investigated the impact of promotion on job performance at the Tanzania Police School in Moshi. Utilizing a convergent research design, it combined qualitative and quantitative methods, focusing on a population of 450 police officers. A sample size of 183 was determined using Slovin’s formula. Data collection involved simple random and purposive sampling, with questionnaires for officers and interviews for inspectors. To ensure validity, research instruments were reviewed by university experts, while reliability was established through pilot testing, yielding a Cronbach Alpha value of 0.75, indicating good internal consistency. Data were analyzed using SPSS, employing descriptive statistics such as percentages and frequency, presented in tables. The findings revealed that promotions positively influence police officers' performance. The study concluded that ongoing promotions within Tanzania police schools are essential for enhancing performance. Recommendations included identifying and recognizing rewards for officers to foster motivation and improve job performance.